2019
DOI: 10.1002/jcop.22244
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mentoring relationship quality: Investigation from the perspectives of youth and parent participants in Big Brothers Big Sisters of Canada one‐to‐one mentoring programs

Abstract: Aims This study examined predictors of mentoring relationship quality (MRQ) as reported by youth and parents participating in Big Brothers Big Sisters (BBBS) of Canada one‐to‐one mentoring programs. Methods Mentoring program capacity and other external supports, youth personal and environmental risk, youth and parent attitudes and motives, and mentoring relationship processes and attributes were examined as predictors of MRQ at 18 months following youth referral to the program using data from a longitudinal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…This finding is interesting, given that the average match length for BBBS America is 11.4 months [ 36 ]. Longer relationships and few or minimal match difficulties were positively correlated with higher relationship quality, as reported by parents and mentees among adolescents from 20 agencies from BBBS Canada [ 37 ] and mentees in mentoring programs in Sweden [ 38 ]. In their Swedish study, Larsson et al [ 39 ] demonstrated the importance of sufficient duration in a study conducted in a mentoring program that lasts for at least one year.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is interesting, given that the average match length for BBBS America is 11.4 months [ 36 ]. Longer relationships and few or minimal match difficulties were positively correlated with higher relationship quality, as reported by parents and mentees among adolescents from 20 agencies from BBBS Canada [ 37 ] and mentees in mentoring programs in Sweden [ 38 ]. In their Swedish study, Larsson et al [ 39 ] demonstrated the importance of sufficient duration in a study conducted in a mentoring program that lasts for at least one year.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, discussions about family and friends were related to the quality of the mentor relationship as perceived by the mentors, whereas discussions about school and future plans were significant predictors of relationship quality according to the mentees’ reports [ 70 ]. Mentors’ emotional support, rather than mentors’ instrumental support, predicted the quality of the relationship as perceived by the mentees [ 37 ]. More CBM mentors reported feelings of closeness toward their mentees than SBM mentors in BBBS of America [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…School factors received much less attention from scholars than programme characteristics (De Wit et al, 2019). This study revealed that the degree of appropriateness of the setting where mentors and mentees meet is related to greater relationship quality.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an interpersonal history of poor relationships with adults may hinder the possibility that mentees develop trust and connection with an assigned mentor (Kobak & Sceery, 1988; Larose, Tarabulsy, & Cyrenne, 2005), whereas socially skilled youths have been found to be more likely to connect with adults (Morison & Masten, 1991; Spencer, 2007a). At the micro‐social level, there is evidence that mentees' family characteristics and perceptions of the match are related to relationship strength (De Wit, DuBois, Erdem, Larose, & Lipman, 2019; Shamblen, Courser, Schweinhart, & Thompson, 2020). At the programme level, the quality of the programme and the support offered to mentors are considered a benchmark for effective mentoring programmes (Herrera & Karcher, 2013; MENTOR, 2015).…”
Section: Relationship Quality In Mentoring Programmesmentioning
confidence: 99%
“…Closeness between mentor and mentee is often how relationship quality in mentoring is specified (e.g., De Wit et al, 2019; Lyons et al, 2019; Raposa et al, 2016; Rhodes, 2005). Closeness, in this sense, refers to mentees’ feeling of a close bond with their mentor, and of being able to share (negative) experiences and concerns.…”
Section: Introductionmentioning
confidence: 99%